Social linguistics and literacies : ideology in discourses - Gee, James Paul (Routledge, 2012)
In its first edition, Social Linguistics and Literacies was a major contribution to the emerging interdisciplinary field of sociocultural approaches to language and literacy, and was one of the founding texts of the 'New Literacy Studies'. This book serves as a classic introduction to the study of language, learning and literacy in their social, cultural and political contexts. It shows how contemporary sociocultural approaches to language and literacy emerged and: * Engages with topics such as orality and literacy, the history of literacy, the nature of discourse analysis and social theories of mind and meaning * Explores how language functions in a society * Surveys the notion of 'discourse' with specific reference to cross-cultural issues in communities and schools. This new edition incorporates contemporary work on "new literacies", that is, meaning making that uses digital media, images, or "multimodal texts" which integrate words and images. This new perspective fully updates the book and its approach to language, learning, and literacy in society and culture. It will be of interest to researchers, lecturers and students in education, linguistics, or any field that deals with language, especially in social or cultural terms